2017
DOI: 10.1021/acs.jpclett.7b02818
|View full text |Cite
|
Sign up to set email alerts
|

Optical Antenna-Based Fluorescence Correlation Spectroscopy to Probe the Nanoscale Dynamics of Biological Membranes

Abstract: The plasma membrane of living cells is compartmentalized at multiple spatial scales ranging from the nano- to the mesoscale. This nonrandom organization is crucial for a large number of cellular functions. At the nanoscale, cell membranes organize into dynamic nanoassemblies enriched by cholesterol, sphingolipids, and certain types of proteins. Investigating these nanoassemblies known as lipid rafts is of paramount interest in fundamental cell biology. However, this goal requires simultaneous nanometer spatial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 133 publications
1
46
0
1
Order By: Relevance
“…[1][2][3][4] This inhomogeneity gives rise to the concept of lipid ras which are assumed to be nanoscale domains of lipids and proteins in the membrane. [1][2][3][4][5][6] Lipid ra formation is thought to be important for various cellular processes. 5,6 To explore membrane properties, bilayers made from synthetic lipids are oen used.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] This inhomogeneity gives rise to the concept of lipid ras which are assumed to be nanoscale domains of lipids and proteins in the membrane. [1][2][3][4][5][6] Lipid ra formation is thought to be important for various cellular processes. 5,6 To explore membrane properties, bilayers made from synthetic lipids are oen used.…”
Section: Introductionmentioning
confidence: 99%
“…On these grounds, sorting of proteins in rafts may restrict or potentiate signaling cross-talk. Membrane rafts are assumed to be transient and dynamic structures (90,91), and advanced imaging techniques have revealed that several signaling molecules are transiently recruited to membrane domains with the aid of protein-protein, protein-lipid, and/or lipid-lipid interactions (23, [92][93][94][95]. This transient and dynamic spatial compartmentalization of signaling pathways in lipid rafts provides a high flexibility and plasticity in signal transduction.…”
Section: Spatial Compartmentalization Of Signaling Pathways In Lipid mentioning
confidence: 99%
“…Mesoscopic vibrational and relaxational dynamics of phospholipid bilayers are described by Brillouin light, inelastic X‐ray, and neutron scattering spectroscopies. Also, molecular dynamics are studied by experimental methods using probes, like fluorescence spectroscopy or electron spin resonance …”
Section: Introductionmentioning
confidence: 99%
“…Phospholipid bilayers, being models of plasma membrane of living cells and perspective materials for drug delivery systems, are popular subjects of research studies. [1][2][3][4][5][6][7][8][9] Phospholipid bilayer structure is studied by Xray and neutron scattering techniques, [10,11] and by cryogenic electron microscopy, [12] lipid-order parameters can be described also by nuclear magnetic resonance method. [13,14] Differential scanning calorimetry allows to extract the entropies and temperatures of phase transitions in phospholipid bilayers, the most important being the transition from ordered low-temperature gel state to disordered fluid (liquid crystalline) state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation